2011
DOI: 10.1111/j.1365-2753.2011.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased payment for ventilation tube insertion on decision making for paediatric otitis media with effusion

Abstract: The waiting time of VTI for children with otitis media with effusion (OME) has not been shortened after the increase in VTI payment. Waiting time in private hospitals is shorter than that in public hospitals. Increased payment for VTI has no effect on the physicians' decision making regarding to waiting time for children with OME in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The rate of tympanostomy tube insertion and tube re-sinsertion of children in Taiwan is low. This may be because Asian parents usually do not like their children to undergo surgery, leading to more conservative management or otolarygologists in Taiwan managed pediatric otitis media more conservatively under the suggestions of clinical practice guideline in comparison to surgeons in the United States [44][46].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of tympanostomy tube insertion and tube re-sinsertion of children in Taiwan is low. This may be because Asian parents usually do not like their children to undergo surgery, leading to more conservative management or otolarygologists in Taiwan managed pediatric otitis media more conservatively under the suggestions of clinical practice guideline in comparison to surgeons in the United States [44][46].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing trend of tympanostomy tube insertion in Taiwan, we have a lower rate of tympanostomy tube insertion in comparison with that in the United States and Europe [ 64 66 ]. The reasons may be that surgical interventions are not favorable choices of Taiwanese parents, leading to more conservative management, or otolaryngologists in Taiwan adhered more to the suggestions of clinical practice guideline in comparison to surgeons in the United States on treatment of pediatric otitis media with effusion [ 67 69 ]. For previous studies analyzing observational database, several of them also found protective effect PCV on otitis media for children [ 9 , 37 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…1). 24 The episode of OME 6 months before the date of surgery was considered as previous episode of OME for recurrence pediatric OME is very common. The ICD-9 codes we used were shown in the Supplementary Appendix, http://links.lww.com/JCMA/A147.…”
Section: Methodsmentioning
confidence: 99%